Learning styles and pedagogy in post-16 learning: a systematic and critical review - Coffield, Franck; Moseley, David; Hall, Ela; Ecclestone, Kathryn (Learning & Skills Research Centre, 2004)
Learning style instruments are widely used but not enough is known about their reliability and validity and their impact on pedagogy in post-16 learning. This report documents work from a project commissioned by the Learning and Skills Development Agency (LSDA) to carry out an extensive review of research on post-16 learning styles, to evaluate the main models of learning styles, and to discuss the implications of learning styles for post-16 teaching and learning. The following research questions were addressed: What models of learning styles are influential and potentially influential?...